SEJARAH PERKEMBANGAN IKHWANUL MUSLIMIN DAN DAKWAHNYA - rodiah sari anwar (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Hasan Albanna was the founding figure of the Muslim Brotherhood, he grew up in the city of Delta Egypt, Muhammadiyah. His father was a parasier, and the ulama, as was common in Egyptian society, Hasan followed in his father's footsteps. Hasan Albanna studied and received religious education from his father. At the age of 12, Hasan Albanna entered elementary school. Hasan Albanna then joined the group, namely the munkar prevention group. This association emphasizes explaining Islamic rituals and morality completely, and sends letters of threat to those found to violate Islamic standards. The view of the Muslim Brotherhood of da'wah is compensitive and universal, Islamic da'wah is not limited to only one not just so that each side gets a balanced portion, but Islamic da'wah affirms all sides and tries to make it happen both mind, spiritually, heart and body . The aspects of Islamic da'wah that are of concern are thought, morals, jihad, social politics, and culture.